Gastrointestinal parasites as a possible threat to an endangered autochthonous Portuguese sheep breed. (2020) - Ruano, Z.M.; Cortinhas, A.; Carolino, N.; Gomes, J.; Costa, M.; Mateus, T.L.
Abstract: Helminth and protozoan infections are responsible for important diseases in grazing sheep, which can be especially threatening in an autochthonous breed at risk of extinction like the Churra Galega Mirandesa Portuguese sheep breed. The aim of the present study was to determine the diversity, prevalence and burden of gastrointestinal parasites in these sheep and to assess the effects of deworming practices, cohabiting animals on the farm and feed management. Coprological qualitative and quantitative analysis (flotation, natural sedimentation and McMaster method) were used to identify and quantify gastrointestinal parasites and a questionnaire was designed and applied. A total of 512 faecal samples were collected from 49 flocks, and 49 replies to the questionnaire were received. Parasites were identified in 100% of the flocks, and in 97% of the samples. The genera or species that have been morphologically identified were: strongyle-type, Nematodirus spp., Skrjabinema spp., Moniezia expansa, Moniezia benedeni, Trichuris spp., Capillaria spp., Eimeria spp., Dicrocoelium spp. and Fasciola hepatica. This is the first report in Portugal of Skrjabinema spp. The burden of parasites' oocysts and eggs per gram in faecal samples ranged, respectively, from 50 to 17, 550 for Eimeria spp., and from 50 to 6250 for strongyle-type eggs. Factors affecting parasitic infections were evaluated using a multivariate logistic regression. Grazing time and a lack of anthelmintic treatment were positively associated with Nematodirus spp. infection. This study showed that there is a high prevalence and diversity of gastrointestinal parasites in the Churra Galega Mirandesa sheep breed.